Teaching Of English In The Rural Belt Of Arunachal Pradesh: A Brief Analysis - Subhashis Banerjee (Elementary Education Online, 2023)
This paper seeks to bring issues related to the problem of teaching English in the rural belt of Arunachal Pradesh. Language policy in schooling turned out to be a social and personal matter. The quality of English teaching in most Indian schools paints a very frightening picture. The language skills of teachers, the use of language and teaching materials are key concerns for quality learning of English. In reality, the situation for rural students of this state is very difficult. Students from cities like Itanagar had the access of language labs, audio-visual materials, etc., so they had no choice. In general, the students of this section see English as a subject rather than a language. That’s the main obstacle for them. The majority of students read only English for exams. They are not familiar with how to recite poetry, but they know how to memorize them. In fact, rural students are not good at English. On the other hand, many teachers do not have a long-term vision of their students’ lives. They are focused only on exams. Language serves as a tool to express ourselves effectively in a variety of communication situations. However, it is a second language that requires conscious, deliberate and systematic effort to learn or acquire. Acquiring a second language is a major challenge for any native speaker who works with this language.